Vonoprazan-amoxicillin combination therapy for Helicobacter pylori eradication: an umbrella review of meta-analyses - Saif Syed; Fatima Tu Zehra; Maham Zaman; Vikash Kumar Karmani; Ayesha Saleem; Momina Khalid; Syeda Nimrah Asim; Sara Izhar; Gaurang Hasmukhbhai Suhagiya (SpringerOpen, 2024)
Abstract Background This umbrella review aims to synthesize evidence from previously conducted meta-analyses and review articles to assess the effects of vonoprazan-amoxicillin (VA) in the management of Helicobacter pylori (Hp). Methods While adhering to the PRIOR guidelines, PubMed, Google Scholar, Web of Science, and Scopus were searched from the database inception to May 2024 to identify relevant articles. The outcomes of interest included eradication rate, compliance, and adverse events. The risk ratios for these outcomes were compared across the studies and a corrected covered area (CCA) assessment was performed to determine overlap. Each included review was assessed for its quality and rigor via the AMSTAR-2 tool. Results From 13,743 articles identified during the literature search, 4 meta-analyses were included. A significant overlap was noted across studies with a corrected cover area of 20.8%. VA dual therapy outperformed PPI-based therapies in eradication rates (RR: 1.14-1.15, p < 0.05), but showed no significant difference compared to vonoprazan-amoxicillin-clarithromycin (VAC) triple therapy (RR: 0.95-0.97, p > 0.05). Compliance was significantly higher with VA dual therapy versus proton pump inhibitors (PPI)-based therapies (RR: 1.14, p = 0.004), but no significant difference was found between VA dual therapy and VAC therapy. Adverse events were reported inconsistently: one review found a higher likelihood with VA dual therapy versus PPI-based therapies (RR: 1.14, p = 0.0004), while others reported lower risk (RR: 0.59-0.80). VA dual therapy has not shown significant adverse events versus VAC therapy. Conclusion VA dual therapy presents as a promising alternative to PPI-based therapies, showcasing better eradication rates and higher compliance. Its performance is comparable to VAC triple therapy, indicating its potential as an effective treatment option for certain conditions.